NOVEL METHODS FOR THE ASSESSMENT OF CRACK PROPAGATION IN ENDODONTICALLY TREATED TEETH - Еkaterina Karteva; Neshka Manchorova-Veleva; Vesela Stefanova; Marin Atanasov; Angel Atanasov; Dessislava Pashkouleva; Petya Kanazirska; Tsvetanka Babeva; Violeta Madjarova; Stoyan Vladimirov (Peytchinski Publishing, 2016)
Background: Vertical root fractures (VRF) can be defined as either complete or incomplete fractures that occur predominantly in endodontically treated teeth (ETT). The clinical symptoms and conventional radiographic techniques are not always accurate, which can lead to diagnostic errors. This motivated us to seek new, better techniques that can improve the prognosis and treatment of ETT with vertical fractures. Objective: The aim of this study was to investigate the potential of three novel techniques: Cone Beam Computed Tomography (CBCT), Optical Computed Tomography (OCT) and 3D Profilometry for the visualization and assessment of VRF. Methods: The study involved intact human premolars, extracted for orthodontic or periodontal reasons. The teeth were then endodontically treated and restored with prefabricated metal posts. No additional preparation of the coronal hard dental tissues was performed, apart from the access cavity. After thermocycling, their fracture resistance was evaluated in a standard testing machine. The resulted vertical fractures and crack propagation were evaluated using CBCT, OCT and 3D Profilometry. Results: The CBCT provided visualization of the tooth in three planes: axial, coronal and sagittal. Root fractures were observed at the coronal and middle 1/3 of the root. The OCT provided highly-detailed, biomicroscopic cross-sectional images of the mesial and distal root surfaces. The images, obtained with 3D Profilometry showed the surface topography and provided precise information about the width and depth of the VRF. Conclusion: All of the techniques used in this study proved to be highly informative, non-invasive and non-contact methods, suitable for the evaluation of VRF.